2014
DOI: 10.1111/bjd.13363
|View full text |Cite
|
Sign up to set email alerts
|

A telephone-based motivational interviewing intervention has positive effects on psoriasis severity and self-management: a randomized controlled trial

Abstract: A 3-month motivational interviewing intervention following CHT had positive overall effects on disease severity, self-efficacy, psoriasis knowledge and health behaviour change. This approach has the potential to be an important complement to medical management, self-management and education in patients with psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 51 publications
1
54
0
1
Order By: Relevance
“…We found a significant association between HL and self‐efficacy in all the HLQ scales. Knowing the value of self‐efficacy to attain self‐management this is an important finding that supports previous research . Patients with higher HL may feel more confident in their ability to pursue self‐management behaviours and may be more likely to perform them .…”
Section: Discussionsupporting
confidence: 81%
“…We found a significant association between HL and self‐efficacy in all the HLQ scales. Knowing the value of self‐efficacy to attain self‐management this is an important finding that supports previous research . Patients with higher HL may feel more confident in their ability to pursue self‐management behaviours and may be more likely to perform them .…”
Section: Discussionsupporting
confidence: 81%
“…The final instrument has eight scales, which have been translated and culturally adapted into over 20 languages, and are currently being applied in clinical trials worldwide, including in Norway [12][13][14][15]. However, only a few studies have reported the psychometric performance of the heiQ in the diverse settings, in which it is being applied [16][17][18][19][20][21][22].…”
Section: Making Robust Decisions About the Impact Of Health Educationmentioning
confidence: 99%
“…This builds up the nomothetic web around the questionnaire and self-management across settings, and should give researchers, program implementers and policymakers the confidence that the heiQ will deliver reliable information on program outcomes and will support quality improvement activities. The heiQ has revealed effects in studies with different health care programs [e.g 14,15], and this is likely due to the scales being sensitive to meaningful and relevant outcomes for people participating in self-management programs. …”
Section: Practice Implicationsmentioning
confidence: 99%
“…Brief MI interventions have proved successful in health settings but effectiveness in dermatology care is untested. In this issue of the BJD, Larsen et al . conducted an RCT to evaluate a 3‐month MI intervention for patients with psoriasis post climate therapy/heliotherapy (CHT, an established 3‐week, multidisciplinary therapeutic programme embracing measured sunlight exposure, physical exercise, group interactions and extensive education).…”
mentioning
confidence: 99%
“…Furthermore, a description of the intervention that is sufficient to enable replication has been provided. In all, the study by Larsen et al . concludes that MI may be a useful adjunct to medical management, patient education and self‐management in psoriasis care.…”
mentioning
confidence: 99%